2012
DOI: 10.1029/2012gl052540
|View full text |Cite
|
Sign up to set email alerts
|

Singing‐sand avalanches without dunes

Abstract: Singing‐sand dunes have attracted curiosity for centuries and are now the subject of controversy. We address here two aspects of this controversy: first the possible link between the frequency heard and the shear rate (for a gravity avalanche on a dune slip‐face, scaling as 0.4g/d , with d the ‘mean’ grain diameter), and second, the assumed necessity of a layered dune structure under the avalanche that acts as a resonator. Field recordings of singing dunes over the world reveal that they can present very diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The model can account for the modes of vibration but not for the low frequency content. However, not long after the publication of this study, Dagois-Bohy et al [6] and Dagois-Bohy et al [7] brought booming sand to their laboratory and demonstrated that an avalanche of about 2 cm in thickness on an inclined plane could produce the frequency spectra observed during a natural avalanche on a dune slip face. Furthermore, it is not evident that the theoretical models proposed by Andreotti [2] and Andreotti and Bonneau [8] could predict the observed frequency spectra and more so the low frequency content during a free avalanche on a dune slip face.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The model can account for the modes of vibration but not for the low frequency content. However, not long after the publication of this study, Dagois-Bohy et al [6] and Dagois-Bohy et al [7] brought booming sand to their laboratory and demonstrated that an avalanche of about 2 cm in thickness on an inclined plane could produce the frequency spectra observed during a natural avalanche on a dune slip face. Furthermore, it is not evident that the theoretical models proposed by Andreotti [2] and Andreotti and Bonneau [8] could predict the observed frequency spectra and more so the low frequency content during a free avalanche on a dune slip face.…”
Section: Introductionmentioning
confidence: 71%
“…There is a faint evidence of such a low frequency content in Fig. 1 in Dagois-Bohy et al [7] at time equal to 6 and 17 s. There is no low frequency content in the reports by Hunt and Vriend [5] and by Vriend et al [23] but that could be due to geophone cut-off frequency at around 25 Hz.…”
Section: Freely Avalanching Booming Sandmentioning
confidence: 85%
See 1 more Smart Citation
“…5 Similar broadband sounds have also been recorded in the laboratory using a rotating bed moving past a fixed paddle. 11,12 Douady et al 11 and Dagois-Bohy, Courrech du Pont, and Douady 9 observed that the frequency of burping sounds depends on the shear rate and the particle diameter of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Such sounds were noted by Charles Darwin from his time in Chile in 1835 (see the review of booming sand dunes by Hunt and Vriend 2010). Darwin speculated that the sound was the result of sand avalanching (Dagois-Bohy et al, 2012). Criswell et al (1975) presented the first analysis of the sounds generated by experimenters deliberately disturbing dune flanks.…”
Section: Introductionmentioning
confidence: 99%